2021
DOI: 10.2166/ws.2021.376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Karkheh Dam construction on haze generation due to geomorphological changes in the Khuzestan Province, Southwest Iran

Abstract: An important factor for occurrence of dust storms is the construction of the Karkheh Dam in the Khuzestan province of Iran. It has reduced the annual mean of flow discharge in the Karkheh River from 120 to 50 m3/s and dried lands around river. The area of dried lands is 90.17 km2 around river and 333.45 km2 in the Hawr-al-Azim wetland. The Rosgen method, Fluvial-12 software, Shulits equation showed instability of the plan, cross sections of river and longitudinal slope of river, respectively, around Pay-e-pol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In a study about the distribution of dust storms in Iran Raski [8], found that it has increased in the west of Iran induced by human activity and changes in landforms such as building dams which are in agreement with Adib & Akhzari [9]. Hamzeh [10] studied the effects of drought on dust storms in the western part of Iran and found that Syria and Iraq are centers of dust production and indicate the variation of climatic parameters has effects on dust storms.…”
Section: Anthropogenic Parametersmentioning
confidence: 61%
“…In a study about the distribution of dust storms in Iran Raski [8], found that it has increased in the west of Iran induced by human activity and changes in landforms such as building dams which are in agreement with Adib & Akhzari [9]. Hamzeh [10] studied the effects of drought on dust storms in the western part of Iran and found that Syria and Iraq are centers of dust production and indicate the variation of climatic parameters has effects on dust storms.…”
Section: Anthropogenic Parametersmentioning
confidence: 61%